Development of Student Worksheets to Improve Analytical Thinking Skills on Reaction Rate Material Through the Inquiry Learning Model - Shobakhah, Kholfina Fitrotis; Suyono*, Suyono; Arivi, Maharani Agustina (Jurnal IPA & Pembelajaran IPA, 2025)
Analytical thinking skills (ATS) play a vital role in enhancing the quality of education in Indonesia. This study aims to design student worksheets that foster analytical thinking through an inquiry-based learning model on reaction rate topics. The feasibility of the worksheets is assessed based on three main aspects: validity, practicality, and effectiveness. The validity aspect is examined in terms of content and construct validity. This research applies the ADDIE model approach, but the focus is limited to the development stage. The respondents were 30 students of class XI-6 SMA Negeri 1 Sidayu Gresik. The results indicated that, from the perspective of validity, both content and construct criteria received a minimum score of 4 from all three validators. The feasibility of the practicality aspect is demonstrated by a 98% score from the student response questionnaire, categorising it as practical. This is further supported by student activity observation results, which reached 95%. Meanwhile, the feasibility of the effectiveness aspect is determined through an ATS test, which is analysed using the Wilcoxon signed rank test. The test results show a one tailed p-value of 0.000 (0.05), indicating that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This implies a significant improvement in student scores before and after using the worksheets